Switch From Fetal to Adult SCN5A Isoform in Human Induced Pluripotent Stem Cell–Derived Cardiomyocytes Unmasks the Cellular Phenotype of a Conduction Disease–Causing Mutation. Issue 7 (24th July 2017) - Veerman, Christiaan C.; Mengarelli, Isabella; Lodder, Elisabeth M.; Kosmidis, Georgios; Bellin, Milena; Zhang, Miao; Dittmann, Sven; Guan, Kaomei; Wilde, Arthur A. M.; Schulze‐Bahr, Eric; Greber, Boris; Bezzina, Connie R.; et al.
Abstract : Background: Human induced pluripotent stem cell–derived cardiomyocytes (hiPSC‐CMs) can recapitulate features of ion channel mutations causing inherited rhythm disease. However, the lack of maturity of these cells is considered a significant limitation of the model. Prolonged culture of hiPSC‐CMs promotes maturation of these cells. We studied the electrophysiological effects of the I230T mutation in the sodium channel gene SCN5A in hiPSC‐CMs generated from a homozygous (I230T homo ) and a heterozygous (I230T het ) individual from a family with recessive cardiac conduction disease. Since the I230T mutation occurs in the developmentally regulated "adult" isoform of SCN5A, we investigated the relationship between the expression fraction of the adult SCN5A isoform and the electrophysiological phenotype at different time points in culture. Methods and Results: After a culture period of 20 days, sodium current ( I N a ) was mildly reduced in I230T homo hiPSC‐CMs compared with control hiPSC‐CMs, while I230T het hiPSC‐CMs displayed no reduction in I N a . This coincided with a relatively high expression fraction of the "fetal" SCN5A isoform compared with the adult isoform as measured by quantitative polymerase chain reaction. Following prolonged culture to 66 days, the fraction of adult SCN5A isoform increased; this was paralleled by a marked decrease in I N a in I230T homo hiPSC‐CMs, in line with the severe clinical phenotype in homozygous patients. At this time in culture, I230T het hiPSC‐CMs displayed an intermediate loss of I N a, compatible with a gene dosage effect. Conclusions: Prolonged culture of hiPSC‐CMs leads to an increased expression fraction of the adult sodium channel isoform. This new aspect of electrophysiological immaturity should be taken into account in studies that focus on the effects of SCN5A mutations in hiPSC‐CMs.